Current state and property study of Chinese female elite reserve long jumpers - Xu, S. H.; Tan, H.; Feng, B. Y.; Xu, C. F. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Although the achievements of Chinese female long jumpers are in the top position in Asia, there is great difference compared with world-class jumpers, especially greater differences exist among reserve athletes. The main cause of this gap may be the technique of long jump. This study selected 15 female elite reserve long jumpers (achieved from 6.5m to 6.7m) as the subjects, and a high-speed camera was used to measure their kinetic characteristics during last two strides of the run-up and during take-off.